2010
DOI: 10.1182/blood-2009-11-251231
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide enhances immunity by modulating the balance of dendritic cell subsets in lymphoid organs

Abstract: Cyclophosphamide (CTX), a commonly used chemotherapeutic agent can enhance immune responses. The ability of CTX to promote the proliferation of effector T cells and abrogate the function of regulatory T cells (Tregs) has been described. In this study, we examined the effects of CTX treatment on dendritic cell (DC) subsets and the subsequent outcome on the effector and suppressive arms of adaptive immunity. In secondary lymphoid tissues, tissue-derived migratory DCs (migratory DCs), lymphoid tissueresident DCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 47 publications
4
71
0
2
Order By: Relevance
“…CTX exerted its effects preferentially on the CD8a-expressing-DC subset, determining an initial ablation of lymphoid organ-resident CD8a þ DCs, followed by overshoot replenishment after drug discontinuation. 20,21 Data from our laboratory have revealed that, after CTX administration, CD8a þ DCs migrate to the tumor site where they cross-present tumor-associated antigen ( Figure 2). The platinum-based compound cisplatin was also reported to modulate the percentages of myeloid cells by increasing DCs and eliminating myeloid-derived suppressor cells (MDSCs), thus favoring immune effector responses in melanoma-bearing mice.…”
Section: Effects On the Innate Immune Systemmentioning
confidence: 99%
“…CTX exerted its effects preferentially on the CD8a-expressing-DC subset, determining an initial ablation of lymphoid organ-resident CD8a þ DCs, followed by overshoot replenishment after drug discontinuation. 20,21 Data from our laboratory have revealed that, after CTX administration, CD8a þ DCs migrate to the tumor site where they cross-present tumor-associated antigen ( Figure 2). The platinum-based compound cisplatin was also reported to modulate the percentages of myeloid cells by increasing DCs and eliminating myeloid-derived suppressor cells (MDSCs), thus favoring immune effector responses in melanoma-bearing mice.…”
Section: Effects On the Innate Immune Systemmentioning
confidence: 99%
“…The cyclophosphamide 20 was purchased from Sigma-Aldrich (St Louis, MO, USA) and dissolved in 0.9% normal saline (NS) according to the manufacturer's instructions. The fluorescein isothiocyanate anti-mouse CD4 monoclonal antibody (mAb) and phycoerythrin anti-mouse CD25 mAb were purchased from eBioscience (San Diego, CA, USA).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…20,40,[42][43][44] In cancer patients, immunotherapy that specifically targets Tregs may fail or be insufficient to reverse tumor growth, depending on the cancer type. The efficacy of an immunotherapy depends upon its ability to effectively overcome immune evasion mechanisms and generate new antitumor responses and/or upregulate the existing responses.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Recently, accumulating evidence revealed that antigen processing and presentation by dendritic cells (DCs) were enhanced by certain chemotherapeutic drugs administered at low doses. [9][10][11] Anticancer drugs also have been shown to possess adjuvant activity to stimulate tumor-specific immune responses via the accumulation of DCs at the tumor site and the activation of antigen-specific CTLs during cancer immunotherapy. 12 Moreover, several clinical reports indicated that the combination of immunotherapy with chemotherapeutic agents led to considerable improvement in the survival rate of patients with cancer.…”
Section: Introductionmentioning
confidence: 99%